2022
DOI: 10.3233/jnd-210735
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament Levels in CSF and Serum in an Adult SMA Cohort Treated with Nusinersen

Abstract: Objective: To retrospectively evaluate the utility of serum and cerebrospinal fluid (CSF) levels of neurofilament light chain (NfL) and phosphorylated neurofilament heavy chain (pNfH) as biomarkers for spinal muscular atrophy (SMA) progression and response to nusinersen treatment. Methods: NfL and pNfH levels were quantified using single molecular array (SIMOA) in CSF of 33 adult SMA patients (SMN copy number 3–5) before and in response to nusinersen treatment. In 11 of the patients, blood serum samples were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 55 publications
3
21
0
Order By: Relevance
“…Analysis of neurofilaments in CSF of SMA patients undergoing nusinersen treatment likewise showed a decline in a smaller cohort of young type 1 patients [41] but no significant correlation with motor response in older patients [42][43][44]. Findings of neurofilament analyses are in line with published data [41][42][43]45,46] and validated the quality and validity of our cohort. We observed a consistent and significant decline of pNF-L not only in infants <4 years old as demonstrated earlier [41], but also in older patients with an age range from 6 to 15 years at start of treatment.…”
Section: Con Clus Ionssupporting
confidence: 88%
“…Analysis of neurofilaments in CSF of SMA patients undergoing nusinersen treatment likewise showed a decline in a smaller cohort of young type 1 patients [41] but no significant correlation with motor response in older patients [42][43][44]. Findings of neurofilament analyses are in line with published data [41][42][43]45,46] and validated the quality and validity of our cohort. We observed a consistent and significant decline of pNF-L not only in infants <4 years old as demonstrated earlier [41], but also in older patients with an age range from 6 to 15 years at start of treatment.…”
Section: Con Clus Ionssupporting
confidence: 88%
“…18 In contrast, a few studies measuring neurofilaments in adults with SMA type 2 and 3 have shown contradictory results over a short period of follow-up (6-14 months), making it difficult to interpret the relevance of these biomarkers. [19][20][21][22] In this study, we evaluated both neuroinflammatory and neurodegenerative biomarkers in CSF and serum to assess if they could be used to measure disease progression or even predict therapeutic response as a prognostic marker, as well as how they correlate with each other and to clinical outcome measures in adults with SMA. Additionally, we investigated the effect of nusinersen treatment on a wide range of clinical outcome measures in adults with SMA type 3-4 over a follow-up period of 22 months.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in infants with SMA type 1 showed that pNfH was elevated in plasma and CSF, correlated with multiple indicators of disease severity, and rapidly declined after treatment initiation with nusinersen 18 . In contrast, a few studies measuring neurofilaments in adults with SMA type 2 and 3 have shown contradictory results over a short period of follow‐up (6–14 months), making it difficult to interpret the relevance of these biomarkers 19–22 …”
Section: Introductionmentioning
confidence: 99%
“… 22 cNfL has been found to reflect disease severity and treatment response in pediatric SMA, 23 but still provides limited information in adult SMA because it overlaps with healthy controls and often shows no association with motor improvement. 24 , 25 , 26 , 27 …”
Section: Introductionmentioning
confidence: 99%